2010
DOI: 10.1016/j.nima.2010.02.123
|View full text |Cite
|
Sign up to set email alerts
|

A low-voltage retarding-field Mott polarimeter for photocathode characterization

Abstract: Nuclear physics experiments at Thomas Jefferson National Accelerator Facility's CEBAF rely on high polarization electron beams. We describe a recently commissioned system for prequalifying and studying photocathodes for CEBAF with a load-locked, low-voltage polarized electron source coupled to a compact retarding-field Mott polarimeter. The polarimeter uses simplified electrode structures and operates from 5 to 30 kV. The effective Sherman function for this device has been calibrated by comparison with the CEB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…As mentioned above, the electron beam polarization is related to the measured count asymmetry by / , where the was determined previously to be 0.201 ± 0.005. 20 The value of is a function of ΔE, which is the largest amount of inelastic energy loss an incident electron can have suffered in the target and still be detected by the CEMs. 20,22 This maximum energy loss ΔE can be varied by adjusting the bias voltage applied to grids at the entrance of the CEMs.…”
Section: B Beam Polarization Using Conventional Circularly-polarizedmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the electron beam polarization is related to the measured count asymmetry by / , where the was determined previously to be 0.201 ± 0.005. 20 The value of is a function of ΔE, which is the largest amount of inelastic energy loss an incident electron can have suffered in the target and still be detected by the CEMs. 20,22 This maximum energy loss ΔE can be varied by adjusting the bias voltage applied to grids at the entrance of the CEMs.…”
Section: B Beam Polarization Using Conventional Circularly-polarizedmentioning
confidence: 99%
“…20 The value of is a function of ΔE, which is the largest amount of inelastic energy loss an incident electron can have suffered in the target and still be detected by the CEMs. 20,22 This maximum energy loss ΔE can be varied by adjusting the bias voltage applied to grids at the entrance of the CEMs. The value of increases with 13 decreasing ΔE because inelastic scattering events, which depolarize the detected electrons, are increasingly discriminated against.…”
Section: B Beam Polarization Using Conventional Circularly-polarizedmentioning
confidence: 99%
“…Consequently, many useful references exist in the case when the electron beam energy is that of a DC high voltage electron gun 23 (>50 kV). Another variant, found in the laboratory environment to study polarized sources, is the retarding potential Mott polarimeter [24][25][26] wherein a small accelerating voltage (<50 kV) is applied only for the purpose of Mott scattering. Two useful review papers on low energy Mott scattering may be found in Refs.…”
Section: Mott Polarimetrymentioning
confidence: 99%
“…However, the systematic errors caused by stray fields mean that for exchange scattering polarimeters, it is generally preferable to reorient the magnetization of the polarimeter scattering surface. Measured with JLAB 5 MeV Mott polarimeter, S eff À0.4008, which was calibrated by thickness extrapolation to zero foil thickness Grames et al [47] McCarter et al [55] 42.69 AE 0. 92 100 nm film of GaAs (110) in purpose built polarized electron source Measured using a 120 kV Mott polarimeter Mulhollan et al [293] À83 AE 5 Photoemission from Fe (110) on W(110) at E F P value refers back to Dedkov et al [194] and Kurazawa et al [88], which both then refer back to Raue et al [29] who used a 100 kV Mott polarimeter in which S eff was stated, without further detail, to be 0.16.…”
Section: Instrumental Asymmetry and Its Eliminationmentioning
confidence: 99%